Overview of the Incidence of Dysmenorrhea in Terms of Anemia in Adolescents in the Village: Gambaran Kejadian Dismenorea Ditinjau Dari Anemia Pada Remaja di Desa - Melati, Adella Andi; Hanum, Sri Mukhodim Farida (Universitas Muhammadiyah Sidoarjo, 2020)
The incidence of dysmenorrhea at Fikes Umsida in 2018 reached 85% according to the results of research conducted by Idatul Awaliyah. Dysmenorrhea is pain during menstruation, usually with cramping and centered in the lower abdomen. Dysmenorrhea is caused by many factors, one of which is anemia. The purpose of this study was to describe the incidence of dysmenorrhea in terms of anemia in adolescent girls. This research is a descriptive research with a cross sectional approach. The population is 10 young women in Waru Village who meet the research criteria. The variables in this study were the incidence of dysmenorrhea and anemia. Collecting data on the incidence of dysmenorrhea using a questionnaire and data on Hb levels by means of examination using an Hb Stick. The results showed that half (50%) of adolescent girls had moderate dysmenorrhea and were not anemic, and half (50%) had severe dysmenorrhea and were not anemic, while most (75%) female adolescents had moderate dysmenorrhea with anemia and a small portion (25%) had moderate dysmenorrhea with anemia. ) had severe dysmenorrhea with anemia. So it can be concluded that the incidence of dysmenorrhea with moderate and severe degrees who are not anemic is the same. While the incidence of dysmenorrhea with moderate degree of anemia is more than the incidence of dysmenorrhea with severe degree of anemia.